POPULATION-BASED ANALYSIS AND GRAPHIC INTERPRETATION OF FOSSIL PALYNOMORPH RECORDS FROM PALYNODATA: TAXONOMIC AND BIOSTRATIGRAPHIC IMPLICATIONS - White J.M.; Jessop C.M. (My University, 2002)
Palynodata is a comprehensive database of the occurrences of pre-Quaternary palynomorphs, encompassing over 20#000 publications. Taxa are assumed to have distributions in time and space which are localized to a region around a central point, and, in the idealized case, can be visualized as a bell-shaped curve. A palynological study can be imagined as drawing a sample from each taxon's time/space distribution. The probability of recording any taxon is partly a function of its abundance at the sampled point in the distribution. A comprehensive database such as Palynodata should allow approximation of the underlying population distribution of the taxon. Retrievals show that useful information is recovered from Palynodata, although there are errors and inadequacies in the database, of which the chief is the generalized study locality record. A computer program, Palynoplot, produces graphic plots of retrievals from Palynodata, allowing improved recognition of the patterns and problems in the database. Images of the database may have future applications for palynological taxonomy, paleoclimatology, paleoecology, modelling of palynomorph distributions, and possibly plate tectonic reconstruction.
Keywords: PALYNODATA; DATABASES; PALYNOLOGY; PALYNOMORPHS; BIOSTRATIGRAPHY; PALEONTOLOGY; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная